Business Performance of Tempe Chips SMEs in Sanan Village Testing the Role of Digital Transformation, Marketing Strategy and Business Innovation - Safitri, Heida Ifkari; Winarno, Agung; Rahayu, Wening Patmi (Technium Business and Management, 2025)
Business performance with adequate growth has always been the goal of implementing various business strategies, including SME group entrepreneurs. Not a few in this field, management tries to keep up with the development of its competitive challenges by adapting technology, as well as developing innovations in its business so that it can survive and even grow. This study aims to examine the effect of digital transformation on business performance through marketing strategy and business innovation as mediating variables. The research approach is quantitative causality and is expose facto explanatory, the research location is Kampung Sanan Malang City. extracting data using a closed questionnaire instrument using a 5-option Likert scale with observation. the object of this research is the perpetrators of SMEs Tempe chips Sanan Malang City. This SME was chosen with the consideration that the contribution of this business is very meaningful for the growth of the local economy, but in the last track record its performance is very fluctuating and even tends to fall. Data analysis using Structural Equation Modeling - Partial Least Squares (SEM-PLS 3). The results showed that digital transformation affects business performance, marketing strategy and business innovation. In addition, marketing strategy and business innovation affect business performance, and there is an indirect effect of digital transformation on business performance through marketing strategy and business innovation. This shows that digital transformation is not only focused as a technological tool but also a strategic catalyst in strengthening competitiveness, marketing effectiveness and innovation in running a business. The implications of this research provide a clear picture for SMEs about the importance of adopting digital technology in running a business. Digital transformation is proven to increase business innovation and strengthen marketing strategies that have an impact on improving business performance. Therefore, SMEs need to start or continue to utilize digital platforms such as social media, e-commerce, and digital payment systems to reach a wider market. In addition, it is important for businesses to continue to create innovations, both in the form of products and business processes, in order to compete in an increasingly competitive era. Local governments or related agencies can also use the results of this study as a basis for designing training or mentoring programs on digitalization and innovation for SMEs.